(untitled) (Revista de História da UEG (REVHIST), 2021)
The present work sought to point out how the fields were constituted, taking into account the protagonists of the work on the land, men and women who cultivated in the midst of the adversities of the hinterlands in the south and north of Mato Grosso between the 18th and 19th centuries. Delimiting the analysis of the role of the “poor and free”, a category responsible for working on the land, and still little known and considered by official historiography, it is that we base the bibliographic debate, together with a documentary analysis of the main sources of Portuguese America and Brazil Império, which are respectively: the Relatos Monçoeiros, the “Land Law of 1850” and the daily “Derrotas” by the sertanista Joaquim Francisco Lopes. Keywords: Countryside life. Poor and free. Field.